2008
DOI: 10.1055/s-2007-992926
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome and Endometrial Cancer

Abstract: An association between polycystic ovary syndrome (PCOS) and endometrial carcinoma was first suggested in 1949. Since then, several studies have been published that appear to support this association, and it is common practice among gynecologists and physicians to prescribe hormonal treatment to reduce this perceived risk, although there is no consensus as to the subgroup of PCOS in whom this is required. The mechanism(s) underlying any association are also unclear, but it is again widely assumed that chronic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 43 publications
2
66
0
4
Order By: Relevance
“…PCOS was found to be a significant risk factor predicting malignancy in endometrial polyps. Endometrial hyperplasia is seen in 35 % of women with PCOS who are not receiving either contraceptive steroids or periodic progestin withdrawal [28]. Moreover, those at the highest risk of endometrial hyperplasia are women who have less than 4 menses per year and ultrasound endometrial thickness more than 7 mm [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCOS was found to be a significant risk factor predicting malignancy in endometrial polyps. Endometrial hyperplasia is seen in 35 % of women with PCOS who are not receiving either contraceptive steroids or periodic progestin withdrawal [28]. Moreover, those at the highest risk of endometrial hyperplasia are women who have less than 4 menses per year and ultrasound endometrial thickness more than 7 mm [29].…”
Section: Resultsmentioning
confidence: 99%
“…It is generally assumed that chronic anovulation with unopposed estrogen stimulation of the endometrium is a main factor. Obesity, hyperinsulinemia, hyperandrogenism, and recurrence of AUB after hysteroscopic polypectomy, which are also the features of PCOS, are the risk factors for endometrial malignancy [28,30].…”
Section: Resultsmentioning
confidence: 99%
“…Было продемонстрировано, что женщины с СПКЯ имеют повышенный (почти в 4 раза) риск развития рака эндометрия, в то время как риск развития других ЗНО (рака молочных желез и рака яичников) сопоставим с аналогичным показателем в общей популяции женского населения Дании [13]. Степень риска рака эндометрия у женщин с СПКЯ до сих пор обсуждается [4,26]. Отмечены различия в фенотипе женщин с РЭ при наличии и без СПКЯ.…”
Section: Polycystic Ovary Syndrome (Pcos) Is the Most Common Endocrinunclassified
“…Epidemiological data has demonstrated that obese individuals possess a significantly increased risk of developing endometrial cancer in comparison with non-obese individuals (risk ratio, 6.25; 95% CI, 3.75-10.42; P<0.001) (36). An additional risk factor for endometrial cancer is polycystic ovarian syndrome (PCOS), in which hyperinsulinemia and hyperandrogenism are the two central pathological conditions (37). Metformin has a therapeutic effect on the anovulatory cycle in PCOS (38), and is expected to reduce the carcinogenic risk in endometrial cancer (39).…”
Section: Antitumor Effect Of Metformin In Endometrial Cancermentioning
confidence: 99%